Mapping Publication Trends Related to Islamic Studies during COVID-19 Pandemic - Uspal Jandevi; Gao Shanbing (Journal of Asian Wisdom and Islamic Behavior, 2023)
This paper aims to map and analyze publication trends related to the role of Islamic studies in the emergence of the COVID-19 pandemic. The COVID-19 outbreak that infected the world in 2020 also gave rise to various scientific breakthroughs, not only in the medical field but also in the social sciences and humanities. Sharing the scientific breakthrough was published in various studies which were then published in scientific journals. Therefore, this research was conducted to map out what things in Islamic studies were developed to respond to the emergence of the COVID-19 pandemic throughout the world. This research is included in the systematic literature review category, the data studied in this paper were obtained from the Scopus database with the keywords "Islamic studies" and "Covid-19". Publication manuscripts taken are limited only from 2020 to 2022, the data that has been obtained are then read using the VoSViewer and Bibliometric applications. The results in this study show that research related to Islamic studies and disaster mitigation caused by the COVID-19 outbreak has not yet become a popular research among academics of Islamic studies.